Effects of the Social Conteht of the COVID-19 pandemic on educational policies - Milinković, Jasmina; Banđur, Veljko (Sociološki pregled, 2021)
The social context is one of the determining factors in the creation of educational policies and, in particular, the curriculum. The purpose of this paper is to consider adapting the mathematics curriculum to the current context of the pandemic. Starting from the historical development of the mathematics curriculum in Serbia and the assumption that the conditions in society conditioned the change of the curriculum, the characteristics of the process of planning, organizing and implementing mathematics teaching in a pandemic were ascertained and discussed by a hypothetical deductive method of editing and comparing experiences. The way in which the social context and social institutions influenced the differences between the planned and implemented mathematics curriculum is discussed. It was concluded that the curriculum was redirected towards a modernist approach based on information technologies.
Keywords: (post)modernism; COVID-19; information technologies; communication media; mathematics curriculum